Efficient certificateless searchable encryption scheme with verifiability - Xinhua CUI; Youliang TIAN; Qijia ZHANG (Tongxin xuebao)
Searchable encryption offers an effective way to achieve data privacy protection and keyword search in cloud computing environments.Currently, the existing schemes not only lack dynamic update and efficient verification mechanism, but also suffer from the certificate management burden and key escrow issue.To address these issues, a verifiable multi-keyword searchable encryption scheme based on improved Merkle-Tree had been proposed recently.However, through cryptoanalysis, that scheme could not achieve the indistinguishability.With improvement, an efficient able certificateless searchable encryption scheme with verifiability was proposed.Rigorous analysis show that the proposed scheme not only supports the indistinguishability and the unforgeability, but also enjoys higher computing efficiency and lower communication cost, which is more suitable for terminal devices with limited resources.